2021
DOI: 10.1101/2021.05.05.442810
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The CTPase activity of ParB acts as a timing mechanism to control the dynamics and function of prokaryotic DNA partition complexes

Abstract: SUMMARYDNA partitioning CTPases of the ParB family mediate the segregation of bacterial chromosomes and low-copy number plasmids. They act as DNA-sliding clamps that are loaded at parS motifs in the centromeric region of target DNA molecules and then spread laterally to form large nucleoprotein complexes that serve as docking points for the DNA segregation machinery. Here, we identify conformational changes that underlie the CTP- and parS-dependent closure of ParB clamps. Moreover, we solve crystal structures … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 125 publications
(164 reference statements)
0
6
0
Order By: Relevance
“…S3, B and C; and table S2). The delayed dissociation may originate from nonspecific interaction of the open ParB clamp with the DNA via its positive residue patch at the C terminus ( 31 , 33 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S3, B and C; and table S2). The delayed dissociation may originate from nonspecific interaction of the open ParB clamp with the DNA via its positive residue patch at the C terminus ( 31 , 33 ).…”
Section: Resultsmentioning
confidence: 99%
“…In trans recruitment, in particular, would involve a transient loop formation between two distal segments on the DNA molecule. It has been previously proposed that ParB-like proteins can spread via a similar in trans mechanism ( 38 ), whereas previous work on ParB indicated that long loops may underlie ParB-DNA condensation ( 39 ), particularly at very low forces exerted in magnetic tweezer experiments ( 7 , 31 , 33 ) or DNA curtains ( 10 , 13 ). In our case, a loop would form transiently, and the ParB-ParB dimer-dimer connection would break following the recruitment event.…”
Section: Discussionmentioning
confidence: 99%
“…The predominant fraction of intracellular ParB dimers (> 90%) forms densely packed clusters assembled at parS sites (Sanchez et al, 2015). These ParB condensates exhibit dynamic characteristics, with a high exchange of ParB rate between condensates (Debaugny et al, 2018;Osorio-Valeriano et al, 2021;Tisma et al, 2023). Upon binding to parS and CTP, ParB dimers undergo an important conformational change, transitioning from parS binding to clamping onto flanking DNA (see Figure 1B).…”
Section: Discussionmentioning
confidence: 99%
“…This latter was proposed based on the finding that ParB is a CTPase that clamps over parS DNA and subsequently diffuses along the DNA until the clamp opens (Figure 1B). The physical modeling of ParB DNA profiles through an exponential decay of ParB binding probability along the parS-proximal DNA could depict the 'C&S' on naked DNA (Osorio-Valeriano et al, 2021;Walter et al, 2020). However, this model did not align with some biochemical characteristics of ParB, especially the rates of release from parS and of unloading from the DNA (Walter et al, 2020).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation